FRAUD RISK MANAGEMENT: AN ANTI-FRAUD MODEL FOR TOURIST ACCOMMODATION IN BALI - Nyoman Sunarti; Putu Sukma Kurniawan; Edy Sujana; I Nyoman Putra Yasa (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
This study aims to examine fraud in hotels by developing a Fraud Risk Management (FRM) design. FRM is developed through several stages, including preliminary analysis, preparing the initial design of the FRM, testing the implementation, making correction, and preparing the final design of the FRM. The research method used in this study is a qualitative method by combining Research and Development (R&D) methods. Data collection is done through interview, observation, and documentation techniques. Data analysis method is carired out through data reduction, data presentation, and drawing conclusions. The data sources used in this study are primary data and secondary data. The results of this study show that basically both types of hotels have the same potential for fraud but with different business processes. The FRM design implemented can be divided into 2: general design and specific design. There are some corrections which can finally result in FRM design in accordance with the conditions of each hotel.